Perancangan Sistem Informasi Pendataan Pegawai pada Dinas Lingkungan Hidup Salatiga Berbasis Web Menggunakan Framework Laravel - Setiawan, Kevin; Pakereng, M A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The Environmental Office in the City of Salatiga is a government agency which engaged in the environmental sector. The employee data collection system currently used is still manual by recording data of employee with Microsoft Excel afterwards the data will be stored in a form of archive or printed. By using an ancient method this is certainly less effective due to it will take a lot of time and make the data will be lost easily. Therefore, we need a web-based information system to make all easier for officers to collect employee data. In this study a web-based employee data collection of information system was built using a Laravel Framework. The Laravel Framework is used to make a build system convenient to implement and already provides any kind of features such as database migration and integration unit testing support to supply an easiness for the developers to build applications. This study aims to create an employee data collection information system so that it can be used to facilitate the officers to collect the data of employees at the Environmental Office in the City of Salatiga. The result of this study is showed that by using this kind of application, performance of employee can be improved efficiently.